The Innate Capacity : Mysticism, Psychology, and Philosophy. - Forman, Robert K. C. (Oxford University Press, 1997)
A sequel to Forman's collection "The Problem of Pure Consciousness" (OUP, 1990). The scholars in this book put forward a hypothesis about the cause of mystical, or "pure consciousness" experiences. They look at mystical experience as manifested in a variety of religious and cultural settings.